First-void urine: A potential biomarker source for triage of high-risk human papillomavirus infected women. (September 2017) - Van Keer, Severien; Pattyn, Jade; Tjalma, Wiebren A.A.; Van Ostade, Xaveer; Ieven, Margareta; Van Damme, Pierre; Vorsters, Alex
Abstract: Great interest has been directed towards the use of first-void urine as a liquid biopsy for high-risk human papillomavirus DNA testing. Despite the high correlations established between urinary and cervical infections, human papillomavirus testing is unable to distinguish between productive and transforming high-risk infections that have the tendency to progress to cervical cancer. Thus far, investigations have been primarily confined to the identification of biomarkers for triage of high-risk human papillomavirus-positive women in cervicovaginal specimens and tissue biopsies. This paper reviews urinary biomarkers for cervical cancer and triage of high-risk human papillomavirus infections and elaborates on the opportunities and challenges that have emerged regarding the use of first-void urine as a liquid biopsy for the analysis of both morphological- (conventional cytology and novel immunohistochemical techniques) and molecular-based (HPV16/18 genotyping, host/viral gene methylation, RNA, and proteins) biomarkers. A literature search was performed in PubMed and Web of Science for studies investigating the use of urine as a biomarker source for cervical cancer screening. Five studies were identified reporting on biomarkers that are still in preclinical exploratory or clinical assay development phases and on assessments of non-invasive (urine) samples. Although large-scale validation studies are still needed, we conclude that methylation of both host and viral genes in urine has been proven feasible for use as a molecular cervical cancer triage and screening biomarker in phase two studies. This is especially promising and underscores our hypothesis that human papillomavirus DNA and candidate human and viral biomarkers are washed away with the initial, first-void urine, together with exfoliated cells, debris and impurities that line the urethra opening. Similar to the limitations of self-collected cervicovaginal samples, first-void urine will likely not fulfil the high-quality cellularity standards required for morphological biomarkers. Molecular biomarkers will likely overcome this issue to yield high-throughput, objective, and reproducible results. When using proper sampling, transport, storage, preanalytical biomarker concentration techniques, and clinically validated assays, first-void urine is expected to be a valuable source of molecular biomarkers for cervical cancer screening. Furthermore, as first-void urine can be easily and non-invasively collected, it is a highly preferred technique among women and offers the ability to test both primary high-risk human papillomavirus and biomarkers in the same sample. In addition, the use of first-void urine confers opportunities to reduce loss-to follow-up and non-adherence to screening subjects.